PENGEMBANGAN LKPD BERBASIS LIVEWORKSHEET BERORIENTASI SOAL AKM UNTUK MENGOPTIMALKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Fauziah, Yesi Ulfah; Ratnaningsih, Nani; Lestari, Puji (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2023)
The lack of interactive learning media that is oriented towards AKM questions and based on problem solving has resulted in less than optimal mathematical problem solving abilities of elementary school students. One of the interactive media that can help students understand and solve problems with AKM questions is live worksheet-based LKPD media that is oriented towards AKM questions based on mathematical problem solving. This research aims to determine the procedures for developing interactive learning media, the effectiveness of the media, and determine the increase in students' abilities after using the media. This type of research is R & D (Research & Development) which uses the ADDIE development model. The subjects of this research were 28 students in class V-B at SDN 3 Tugu. Data collection techniques are observation, interviews, questionnaires and tests. Based on the validation results from material experts and media experts, the results were